Mapping gender networks of smartphone addiction and academic procrastination: a network analysis study - Song, Lu; Liu, Zhilin; Yang, Yujia; Yuan, Shuangshuang (Frontiers in Psychology, 2025)
BackgroundSmartphone addiction (SA) and academic procrastination (AP) are two of the educational challenges encountered by many higher education students today that have led to a series of adverse effects on their well-being.Aims, sample, and methodsPrevious studies have reported inconsistent findings regarding gender differences in SA and AP, and limited attention has been paid to gender differences in the interaction between SA and AP. To address this gap, the present study employs network analysis to investigate gender differences in the SA, AP, and SA-AP interaction networks among higher education students. A total of 438 students from four higher education institutions in China participated in this study.ResultsThe findings indicate that there are more differences than similarities in the SA and AP networks between male and female students. In addition, within the SA-AP interaction network, the core feature of the male network is academic procrastination, reflecting deficiencies in time management and self-regulation. In contrast, the core feature of the female network is smartphone addiction, which highlights a strong dependence on immediate social feedback.ConclusionThis study represents the first attempt to investigate gender differences in SA and AP through the lens of network analysis. The findings reveal the complexity of gender differences in behavioral patterns and psychological mechanisms, moving beyond the limitations of previous research that primarily focused on mean-level differences. This study deepens the understanding of SA and AP and provides both theoretical support and practical guidance for the development and implementation of effective intervention strategies to address SA and AP among students.